2021
DOI: 10.1021/acsbiomaterials.0c01705
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Hydrophilic Coating Modification of Intraocular Lens via Facile Dopamine Self-Polymerization for Posterior Capsular Opacification Prevention

Abstract: Posterior capsular opacification (PCO) is the most important complication in cataract phacoemulsification and intraocular lens (IOL) implantation surgery, mainly stemming from the adhesion, proliferation, and transdifferentiation of the postsurgically residual lens epithelial cells (LECs). Previous investigations mainly focused on the hydrophilic surface modification of the IOLs for PCO prevention, such as heparinization. However, the long-term clinical investigations show that there is no significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…With the modification of Exos and Dox@Exos, the WCA of modified IOL surfaces decreases to 34.4° and 32.7°, which shows high hydrophilicity. The excellent hydrophilicity of the surfaces may provide a certain cell anti-adhesion effect [ 18 , 49 , 50 ]. At the same time, the change of WCA further confirms the successful prepared of Dox@Exos modified materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the modification of Exos and Dox@Exos, the WCA of modified IOL surfaces decreases to 34.4° and 32.7°, which shows high hydrophilicity. The excellent hydrophilicity of the surfaces may provide a certain cell anti-adhesion effect [ 18 , 49 , 50 ]. At the same time, the change of WCA further confirms the successful prepared of Dox@Exos modified materials.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the in vivo therapeutic efficacy of the Dox@Exos-modified IOLs, PCO models were constructed on two-month-old Japanese white rabbits by phacoemulsification combined with IOL implantation. The IOLs implantation and postoperative observation were by the methods of our previous publications [ 15 , 48 , 49 ]. The rabbits were treated, monitored, and evaluated according to the Association for Visual and Ophthalmic Research guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…The SCL products typically act passively as coatings or bulking agents at the current stage. In the current translational SCL market, long-term reliability is more important than the functional response capability in commercial applications [365,366].…”
Section: Intelligence and Programmability Of Smart Contact Lens Weara...mentioning
confidence: 99%
“…These two applications have seen recent investigation as a novel method of ocular drug delivery. Liu et al (129) developed an intraocular lens (IOL) with a self-polymerizing polydopamine coating capable of loading and eluting doxorubicin, preventing posterior capsule opacification (PCO) in rabbit models. Jiang et al (130) developed polydopamine nanoparticles which showed effective loading and oxidative stress-dependent release of anti-VEGF in vitro.…”
Section: Other Biopolymersmentioning
confidence: 99%
“…Building off of that research, they found that glutathione may be a useful addition to ascorbic acid in ocular drug delivery (13). Polymer coatings for IOLs, made of polydopamine or synthetic polymers, are being evaluated to reduce complications after cataract surgery from infection and PCO (129,176).…”
Section: Hydrogelsmentioning
confidence: 99%